High-strength flame-retardant material for automobile interior trim panel and preparation method of high-strength flame-retardant material

Through the combination of polypropylene resin, flame retardant and glass fiber reinforcement, high-strength flame retardant materials are prepared, which solves the flammability problem of automotive interior materials, improves the flame retardant performance and production efficiency of the materials, and meets the safety of the automobile industry. and environmental protection requirements.

CN119161663APending Publication Date: 2024-12-20SHANGHAI LANGDOW NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411304860.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The flammability of car interior materials causes fires to spread, threaten the lives of passengers, and produces toxic gases in high temperature environments, affecting health.

Method used

Using polypropylene resin, flame retardant, aniline methyl triethoxysilane and glass fiber reinforced polyethylene terephthalate, high-strength flame retardant materials are prepared through high-mixer mixing and melt extrusion processes to ensure the material uniformity and stability.

Benefits of technology

Improves the mechanical properties, thermal stability and flame retardant properties of the material, enhances the safety and durability of the automotive interior panels, achieves an efficient and stable production process, reduces production costs, and meets environmental protection and sustainable development requirements. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161663A_ABST
    Figure CN119161663A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material preparation, and discloses a high-strength flame-retardant material for an automobile interior trimming panel, which is based on the main components of polypropylene resin, a flame retardant, anilmomethyl triethoxy silane, a reinforcing agent and other additives, and is prepared by the following steps of: extruding a molten mass through a die head according to requirements; and cooling and pelletizing to prepare a granular product, namely the flame-retardant color master batch or the flame-retardant master batch. By accurately controlling the proportion and the mixing process of the raw materials, it is ensured that the final product has high strength, high flame retardance and good stability, polypropylene resin serves as a main material, the flame retardant, the reinforcing agent, anilmomethyl triethoxy silane and other auxiliary components are combined, the mechanical performance, the heat stability and the flame retardance of the material are jointly improved, and the material has good application prospects. Due to the excellent performance, the material has higher safety and durability in the application of automotive trim panels and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a high-strength flame-retardant material for automobile interior trim panels and a preparation method thereof. Background Art

[0002] Automobile interior materials, such as fiber textiles and leather, plastics, rubber and composite materials, are all flammable or combustible materials. These materials are widely distributed in key parts such as automobile roofs, floor mats, door linings, seats, seat belts, luggage compartments, etc., and are in close contact with passengers. Once a fire occurs, the combustion of these materials will spread rapidly, posing a serious threat to the safety of passengers' lives. Interior panel materials, including fiber textiles and leather, plastics, rubber and composite materials, although they provide many conveniences for passengers in terms of aesthetics, comfort and functionality, their inherent flammability or combustibility characteristics cannot be ignored. Existing interior panels are prone to deformation in high temperature environments, and as time goes by, under the continuous rise in temperature, fiber textile materials burn rapidly, the fire spreads easily, and toxic gases may be produced during the combustion process, posing a threat to the health of passengers. Although leather materials are relatively flame resistant, they may still burn rapidly under extreme conditions and are difficult to extinguish after burning. In order to solve this problem, the present invention proposes a new method for preparing high-strength flame retardant materials, which improves this problem by adding glass fiber reinforced polyethylene terephthalate. Summary of the invention

[0003] The object of the present invention is to provide a high-strength flame-retardant material for automobile interior trim panels and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0004] In order to achieve the above object, the present invention provides the following technical solution: a high-strength flame-retardant material for automobile interior panels and a preparation method thereof, characterized in that the main components of the flame-retardant material for automobile interior panels are: polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives, and the mass percentages of the main components are:

[0005] Polypropylene resin 40%-60%

[0006]

[0007] Preferably, the preparation method of the high-strength flame retardant material is:

[0008] S1, preliminary preparation; accurately weigh the basic materials, mix the polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent and other additives in a certain proportion, mix the mixed materials in a high-speed mixer, ensure that all kinds of materials are evenly dispersed, and form a basic composite material;

[0009] Other additives include antioxidants, light stabilizers, lubricants, colorants, antistatic agents and other existing additives, which are common means and techniques used by those skilled in the art and can be appropriately added as needed.

[0010] S2, adding the reinforcing agent: prepare the reinforcing agent whose main component is glass fiber reinforced polyethylene terephthalate, which accounts for 75% of the total reinforcing agent components, and the remaining reinforcing agent components are ethylene-octene copolymer (POE) (accounting for 5%-10%) and ethylene-vinyl acetate copolymer (EVA) (accounting for 15%-20%). According to the proportion, add the reinforcing agent to the previously mixed basic composite material, and mix while adding to ensure that the reinforcing agent is evenly mixed in the basic composite material to avoid local excessive or insufficient addition;

[0011] S3, addition of flame retardant: according to a certain ratio, aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate and polysilane are fully mixed. The proportions of these three materials in the flame retardant are as follows: magnesium hydroxide accounts for 40%-60%, aluminum hydroxide accounts for 10%-15%, ammonium polyphosphate accounts for 5%-15%, and polysilane accounts for 0.05%-0.1%. The mixed materials are added to the previously mixed materials, and mixed while adding to ensure the uniform distribution of these materials. Through the limiting oxygen index (LO I) test, the material should have a high oxygen index value, generally greater than 27, indicating that it is a flame retardant material;

[0012] S4, melt extrusion: melt the mixed materials at a certain temperature (the thermal decomposition temperature of magnesium hydroxide is as high as 340-490 degrees) and adjust the temperature, pressure, screw speed and other parameters of the extruder to ensure that the materials are fully melted and evenly extruded.

[0013] S5, adding antioxidant: adding 0.1%-1% antioxidant to the molten material according to the demand, and stirring fully to make the antioxidant and the molten material fully mixed;

[0014] S6, injection molding: according to the demand, the melt (melting temperature is controlled at 280-300 degrees) is extruded through the die head, and then cooled and pelletized to form granular products, namely flame retardant masterbatch or flame retardant masterbatch. These granules are directly used in the subsequent injection molding and blow molding processes;

[0015] S7, molding: After the flame retardant masterbatch is mixed with the base material in a certain proportion, it is made into automotive interior panels through injection molding, blow molding, and vacuum molding processes. During the molding process, the temperature and pressure parameters need to be controlled to ensure the dimensional accuracy and appearance quality of the product.

[0016] Preferably, the S1 preliminary preparation steps include:

[0017] A1, Material selection and weighing: First, high-quality raw materials need to be carefully selected, including polypropylene resin as the base material. Then, according to the flame retardant grade requirements of the product design, the flame retardant (accounting for 25% of the total material) is accurately weighed. In addition, aniline methyl triethoxysilane is used as a coupling agent or modifier. At the same time, the precise ratio of the reinforcing agent improves the overall strength and stiffness of the composite material. Finally, the additives are added;

[0018] A2, material ratio and mixing: Under the premise of strictly following the formula ratio, the weighed raw materials are fed into the high-speed mixer, and the mixing temperature, speed and mixing time are closely monitored. The polypropylene resin is 60-94 parts, the high-density polyethylene resin is 5-15 parts, and the filler (a mixture of rice husk charcoal and talcum powder) is 0.5-30 parts. The weight ratio of rice husk charcoal to talcum powder is usually 1:110. The average specific surface area of ​​rice husk charcoal is 100500m 2 / g;

[0019] A3, Mixing effect test, to test the mixing effect, including sampling for visual inspection to observe whether the material is uniform and free of lumps.

[0020] Preferably, the main steps of adding the S2 enhancer are:

[0021] B1, reinforcement preparation; according to product design requirements and formula ratio, accurately weigh glass fiber reinforced polyethylene terephthalate, glass fiber reinforced polyethylene terephthalate accounts for 95% of the reinforcement, the selection of glass fiber reinforced polyethylene terephthalate should be based on its specific reinforcement effect on the composite material, and the addition of the reinforcement accounts for 13% of the total ratio;

[0022] B2, addition strategy: including batch-wise, step-by-step addition with thorough mixing after each addition until all the enhancers are completely introduced and evenly dispersed;

[0023] B3, Mixing process monitoring: During the addition and mixing process of glass fiber reinforced polyethylene terephthalate, the mixer speed, mixing time and mixing temperature parameters are adjusted. The processing temperature is roughly between 250℃-280℃ to ensure the smooth mixing process. If local agglomeration or uneven dispersion is found, the mixing parameters should be adjusted in time or other remedial measures should be taken;

[0024] B4, Verification of mixing effect: After the mixing is completed, the mixing effect is fully verified, including physical property testing to evaluate whether the mechanical properties of the composite material meet the expected goals.

[0025] Preferably, the antioxidant in S5 accounts for 5%, and the antioxidant is fully mixed with the material to ensure that the antioxidant accounts for 5% of the total material.

[0026] Preferably, the polypropylene resin is the main material, accounting for 50% of the total weight, and is fully mixed and stirred for fifteen to twenty minutes to form a uniform and stable mixture.

[0027] Preferably, the anilinemethyltriethoxysilane is the secondary auxiliary component, and the proportion mixed with other additives is 12%.

[0028] Preferably, the temperature during melt extrusion in S4 is maintained at 180 to 200 degrees to obtain a high-strength flame retardant material.

[0029] The beneficial effects of the present invention are as follows:

[0030] 1. The present invention ensures that the final product has high strength, high flame retardancy and good stability by precisely controlling the proportion and mixing process of raw materials and adopting a suitable melt extrusion temperature. Polypropylene resin is used as the main material, combined with auxiliary components such as flame retardants, reinforcing agents and aniline methyl triethoxysilane, which jointly improve the mechanical properties, thermal stability and flame retardancy of the material. This excellent performance makes the material have higher safety and durability in applications such as automotive interior panels.

[0031] 2. The present invention realizes an efficient and stable production process by adopting standardized mixing and melting extrusion processes and accurately controlling parameters such as mixing time, mixing temperature and melting extrusion temperature. Long-term mixing and stirring ensures the uniformity and stability of the material, while the appropriate melting extrusion temperature helps to improve production efficiency and reduce fluctuations and uncertainties in the production process. This efficient production process not only reduces production costs, but also improves product yield and consistency.

[0032] 3. The raw materials and additives used in the present invention are mostly environmentally friendly and sustainable. For example, polypropylene resin is a recyclable material, and additives such as anilinemethyltriethoxysilane are also generally low in toxicity and environmentally friendly. In addition, through reasonable formula design and process optimization, the method can reduce the emission and accumulation of harmful substances while ensuring material properties, which meets the requirements of the modern automobile industry for environmental protection and sustainable development. Such environmental protection and sustainability characteristics make the method have broader market prospects and social value in application fields such as automotive interior panels. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] like Figure 1 As shown, the embodiment of the present invention provides a high-strength flame-retardant material for automobile interior panels and a preparation method. The main components of the flame-retardant material for automobile interior panels are: polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives. The mass percentages of the main components are:

[0037]

[0038]

[0039] The preparation method of the high-strength flame-retardant material is as follows: preliminary preparation; accurately weighing the basic materials, mixing the polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives in a certain proportion, mixing the mixed materials in a high-speed mixer, ensuring that the various materials are evenly dispersed to form a basic composite material;

[0040] S2, adding the reinforcing agent: prepare the reinforcing agent whose main component is glass fiber reinforced polyethylene terephthalate, which accounts for 75% of the total reinforcing agent components, and the remaining reinforcing agent components are ethylene-octene copolymer (POE) (accounting for 5%-10%) and ethylene-vinyl acetate copolymer (EVA) (accounting for 15%-20%). According to the proportion, add the reinforcing agent to the previously mixed basic composite material, and mix while adding to ensure that the reinforcing agent is evenly mixed in the basic composite material to avoid local excessive or insufficient addition;

[0041] S3, addition of flame retardant: according to a certain ratio, aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate and polysilane are fully mixed. The proportions of these three materials in the flame retardant are as follows: magnesium hydroxide accounts for 40%-60%, aluminum hydroxide accounts for 10%-15%, ammonium polyphosphate accounts for 5%-15%, and polysilane accounts for 0.05%-0.1%. The mixed materials are added to the previously mixed materials, and mixed while adding to ensure the uniform distribution of these materials. Through the limiting oxygen index (LO I) test, the material should have a high oxygen index value, generally greater than 27, indicating that it is a flame retardant material;

[0042] S4, melt extrusion: melt the mixed materials at a certain temperature (the thermal decomposition temperature of magnesium hydroxide is as high as 340-490 degrees) and adjust the temperature, pressure, screw speed and other parameters of the extruder to ensure that the materials are fully melted and evenly extruded.

[0043] S5, adding antioxidant: adding 0.1%-1% antioxidant to the molten material according to the demand, and stirring fully to make the antioxidant and the molten material fully mixed;

[0044] S6, injection molding: according to the demand, the melt (melting temperature is controlled at 280-300 degrees) is extruded through the die head, and then cooled and pelletized to form granular products, namely flame retardant masterbatch or flame retardant masterbatch. These granules are directly used in the subsequent injection molding and blow molding processes;

[0045] S7, molding: After the flame retardant masterbatch is mixed with the base material in a certain proportion, it is made into automotive interior panels through injection molding, blow molding, and vacuum molding processes. During the molding process, the temperature and pressure parameters need to be controlled to ensure the dimensional accuracy and appearance quality of the product.

[0046] Embodiment 2:

[0047] like Figure 1 As shown, the embodiment of the present invention provides a high-strength flame-retardant material for automobile interior panels and a preparation method. The main components of the flame-retardant material for automobile interior panels are: polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives. The mass percentages of the main components are:

[0048]

[0049] The preparation method of the high-strength flame-retardant material is as follows: preliminary preparation; accurately weighing the basic materials, mixing the polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives in a certain proportion, mixing the mixed materials in a high-speed mixer, ensuring that the various materials are evenly dispersed to form a basic composite material;

[0050] S2, adding the reinforcing agent: prepare the reinforcing agent whose main component is glass fiber reinforced polyethylene terephthalate, which accounts for 70% of the total reinforcing agent components. The remaining reinforcing agent components include ethylene-octene copolymer (POE) (accounting for 5%-10%) and ethylene-vinyl acetate copolymer (EVA) (accounting for 15%-20%). According to the proportion, add the reinforcing agent to the previously mixed basic composite material, and mix while adding to ensure that the reinforcing agent is evenly mixed in the basic composite material to avoid local excessive or insufficient addition;

[0051] S3, addition of flame retardant: according to a certain ratio, aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate and polysilane are fully mixed. The proportions of these three materials in the flame retardant are as follows: magnesium hydroxide accounts for 40%-60%, aluminum hydroxide accounts for 10%-15%, ammonium polyphosphate accounts for 5%-15%, and polysilane accounts for 0.05%-0.1%. Add the mixed materials to the previously mixed materials, and mix while adding to ensure the uniform distribution of these materials. Through the limiting oxygen index (LOI) test, the material should have a high oxygen index value, generally greater than 27, indicating that it is a flame retardant material;

[0052] S4, melt extrusion: melt the mixed materials at a certain temperature (the thermal decomposition temperature of magnesium hydroxide is as high as 340-490 degrees) and adjust the temperature, pressure, screw speed and other parameters of the extruder to ensure that the materials are fully melted and evenly extruded.

[0053] S5, adding antioxidant: adding 0.1%-1% antioxidant to the molten material according to the demand, and stirring fully to make the antioxidant and the molten material fully mixed;

[0054] S6, injection molding: according to the demand, the melt (melting temperature is controlled at 280-300 degrees) is extruded through the die head, and then cooled and pelletized to form granular products, namely flame retardant masterbatch or flame retardant masterbatch. These granules are directly used in the subsequent injection molding and blow molding processes;

[0055] S7, molding: After the flame retardant masterbatch is mixed with the base material in a certain proportion, it is made into automotive interior panels through injection molding, blow molding, and vacuum molding processes. During the molding process, the temperature and pressure parameters need to be controlled to ensure the dimensional accuracy and appearance quality of the product.

[0056] Embodiment three:

[0057] like Figure 1 As shown, the embodiment of the present invention provides a high-strength flame-retardant material for automobile interior panels and a preparation method. The main components of the flame-retardant material for automobile interior panels are: polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives. The mass percentages of the main components are:

[0058]

[0059] The preparation method of the high-strength flame-retardant material is as follows: preliminary preparation; accurately weighing the basic materials, mixing the polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives in a certain proportion, mixing the mixed materials in a high-speed mixer, ensuring that the various materials are evenly dispersed to form a basic composite material;

[0060] S2, adding the reinforcing agent: prepare the reinforcing agent whose main component is glass fiber reinforced polyethylene terephthalate, which accounts for 68% of the total reinforcing agent components. The remaining reinforcing agent components include ethylene-octene copolymer (POE) (accounting for 5%-15%) and ethylene-vinyl acetate copolymer (EVA) (accounting for 15%-25%). According to the proportion, add the reinforcing agent to the previously mixed basic composite material, and mix while adding to ensure that the reinforcing agent is evenly mixed in the basic composite material to avoid local excessive or insufficient addition;

[0061] S3, addition of flame retardant: according to a certain ratio, aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate and polysilane are fully mixed. The proportions of these three materials in the flame retardant are as follows: magnesium hydroxide accounts for 40%-60%, aluminum hydroxide accounts for 10%-15%, ammonium polyphosphate accounts for 5%-15%, and polysilane accounts for 0.05%-0.1%. The mixed materials are added to the previously mixed materials, and mixed while adding to ensure the uniform distribution of these materials. Through the limiting oxygen index (LO I) test, the material should have a high oxygen index value, generally greater than 27, indicating that it is a flame retardant material;

[0062] S4, melt extrusion: melt the mixed materials at a certain temperature (the thermal decomposition temperature of magnesium hydroxide is as high as 340-490 degrees) and adjust the temperature, pressure, screw speed and other parameters of the extruder to ensure that the materials are fully melted and evenly extruded.

[0063] S5, adding antioxidant: adding 0.1%-1% antioxidant to the molten material according to the demand, and stirring fully to make the antioxidant and the molten material fully mixed;

[0064] S6, injection molding: according to the demand, the melt (melting temperature is controlled at 280-300 degrees) is extruded through the die head, and then cooled and pelletized to form granular products, namely flame retardant masterbatch or flame retardant masterbatch. These granules are directly used in the subsequent injection molding and blow molding processes;

[0065] S7, molding: After the flame retardant masterbatch is mixed with the base material in a certain proportion, it is made into automotive interior panels through injection molding, blow molding, and vacuum molding processes. During the molding process, the temperature and pressure parameters need to be controlled to ensure the dimensional accuracy and appearance quality of the product.

[0066] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength flame-retardant material for automobile interior panels, characterized in that: The main components of the flame retardant material for automobile interior panels are: polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent, and other additives. The mass percentages of the main components are:

2. The method for preparing a high-strength flame-retardant material for automobile interior panels according to claim 1, characterized in that: The preparation method of the high-strength flame retardant material is: S1, preliminary preparation; accurately weigh the basic materials, mix the polypropylene resin, flame retardant, aniline methyl triethoxysilane, reinforcing agent and other additives in a certain proportion, mix the mixed materials in a high-speed mixer, ensure that all kinds of materials are evenly dispersed, and form a basic composite material; S2, adding the reinforcing agent: prepare the reinforcing agent whose main component is glass fiber reinforced polyethylene terephthalate, which accounts for 75% of the total reinforcing agent components, and the remaining reinforcing agent components are ethylene-octene copolymer (POE) (accounting for 5%-10%) and ethylene-vinyl acetate copolymer (EVA) (accounting for 15%-20%). According to the proportion, add the reinforcing agent to the previously mixed basic composite material, and mix while adding to ensure that the reinforcing agent is evenly mixed in the basic composite material to avoid local excessive or insufficient addition; S3, addition of flame retardant: according to a certain ratio, aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate and polysilane are fully mixed. The proportions of these three materials in the flame retardant are as follows: magnesium hydroxide accounts for 40%-60%, aluminum hydroxide accounts for 10%-15%, ammonium polyphosphate accounts for 5%-15%, and polysilane accounts for 0.05%-0.1%. Add the mixed materials to the previously mixed materials, and mix while adding to ensure the uniform distribution of these materials. Through the limiting oxygen index (LOI) test, the material should have a high oxygen index value, generally greater than 27, indicating that it is a flame retardant material; S4, melt extrusion: melt the mixed materials at a certain temperature (the thermal decomposition temperature of magnesium hydroxide is as high as 340-490 degrees) and adjust the temperature, pressure, screw speed and other parameters of the extruder to ensure that the materials are fully melted and evenly extruded. S5, adding antioxidant: adding 0.1%-1% antioxidant to the molten material according to the demand, and stirring fully to make the antioxidant and the molten material fully mixed; S6, injection molding: according to the demand, the melt (melting temperature is controlled at 280-300 degrees) is extruded through the die head, and then cooled and pelletized to form granular products, namely flame retardant masterbatch or flame retardant masterbatch. These granules are directly used in the subsequent injection molding and blow molding processes; S7, molding: After the flame retardant masterbatch is mixed with the base material in a certain proportion, it is made into automotive interior panels through injection molding, blow molding, and vacuum molding processes. During the molding process, the temperature and pressure parameters need to be controlled to ensure the dimensional accuracy and appearance quality of the product.

3. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The S1 preliminary preparation steps include: A1, Material selection and weighing: First, high-quality raw materials need to be carefully selected, including polypropylene resin as the base material. Then, according to the flame retardant grade requirements of the product design, the flame retardant (accounting for 25% of the total material) is accurately weighed. In addition, aniline methyl triethoxysilane is used as a coupling agent or modifier. At the same time, the precise ratio of the reinforcing agent improves the overall strength and stiffness of the composite material. Finally, the additives are added; A2, material ratio and mixing: Under the premise of strictly following the formula ratio, the weighed raw materials are fed into the high-speed mixer, and the mixing temperature, speed and mixing time are closely monitored. The polypropylene resin is 60-94 parts, the high-density polyethylene resin is 5-15 parts, and the filler (a mixture of rice husk charcoal and talcum powder) is 0.5-30 parts. The weight ratio of rice husk charcoal to talcum powder is usually 1:

110. The average specific surface area of ​​rice husk charcoal is 100500m 2 / g; A3, Mixing effect test, to test the mixing effect, including sampling for visual inspection to observe whether the material is uniform and free of lumps.

4. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The main steps of adding the S2 enhancer are: B1, reinforcement preparation; according to product design requirements and formula ratio, accurately weigh glass fiber reinforced polyethylene terephthalate, glass fiber reinforced polyethylene terephthalate accounts for 95% of the reinforcement, the selection of glass fiber reinforced polyethylene terephthalate should be based on its specific reinforcement effect on the composite material, and the addition of the reinforcement accounts for 13% of the total ratio; B2, addition strategy: including batch-wise, step-by-step addition with thorough mixing after each addition until all the enhancers are completely introduced and evenly dispersed; B3, Mixing process monitoring: During the addition and mixing process of glass fiber reinforced polyethylene terephthalate, the mixer speed, mixing time and mixing temperature parameters are adjusted. The processing temperature is roughly between 250℃-280℃ to ensure the smooth mixing process. If local agglomeration or uneven dispersion is found, the mixing parameters should be adjusted in time or other remedial measures should be taken; B4, Verification of mixing effect: After the mixing is completed, the mixing effect is fully verified, including physical property testing to evaluate whether the mechanical properties of the composite material meet the expected goals.

5. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The antioxidant in S5 accounts for 5%, and the antioxidant is fully mixed with the material to ensure that the antioxidant accounts for 5% of the total material.

6. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The polypropylene resin is the main material, accounting for 50% of the total weight, and is fully mixed and stirred for fifteen to twenty minutes to form a uniform and stable mixture.

7. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The aniline methyl triethoxysilane is the secondary auxiliary component, and the proportion of the mixed component with other additives is 12%.

8. The method for preparing a high-strength flame-retardant material for automobile interior trim panels according to claim 1, characterized in that: The temperature during melt extrusion in S4 is maintained at 180 to 200 degrees to obtain a high-strength flame-retardant material.